2014
DOI: 10.1371/journal.pone.0096159
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-Response Mappings Shape Inhibition Processes: A Combined EEG-fMRI Study of Contextual Stopping

Abstract: Humans are rarely faced with one simple task, but are typically confronted with complex stimulus constellations and varying stimulus-relevance in a given situation. Through modifying the prototypical stop-signal task and by combined recording and analysis of electroencephalography (EEG) and functional magnetic resonance imaging (fMRI), we studied the effects of stimulus relevance for the generation of a response or its inhibition. Stimulus response mappings were modified by contextual cues, indicating which of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 55 publications
4
18
0
Order By: Relevance
“…Converging evidence from studies with more spatially precise methods such as fMRI (Curtis et al, 2005; Li et al, 2006; Rubia et al, 2001; Swann et al, 2012a) and intracranial recordings (Swann et al, 2009; Swann et al, 2012b) point towards critical roles of pre-SMA and rIFC in simple stopping, in addition to the basal ganglia (Aron and Poldrack, 2006; Ray et al, 2012; Zandbelt and Vink, 2010). Regarding scalp EEG, the majority of studies of successful stopping in the SST reported activity with a fronto-central voltage distribution, similar to what we report here (Etchell et al, 2012; Greenhouse and Wessel, 2013; Johnstone et al, 2007; Kok et al, 2004; Kramer et al, 2011; Lavallee et al, 2014; Nigbur et al, 2011; Schmiedt-Fehr and Basar-Eroglu, 2011; Wessel and Aron, 2013; Yamanaka and Yamamoto, 2010). However, due to the inverse problem, it is still unclear which exact anatomical brain regions generate this fronto-central activity.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Converging evidence from studies with more spatially precise methods such as fMRI (Curtis et al, 2005; Li et al, 2006; Rubia et al, 2001; Swann et al, 2012a) and intracranial recordings (Swann et al, 2009; Swann et al, 2012b) point towards critical roles of pre-SMA and rIFC in simple stopping, in addition to the basal ganglia (Aron and Poldrack, 2006; Ray et al, 2012; Zandbelt and Vink, 2010). Regarding scalp EEG, the majority of studies of successful stopping in the SST reported activity with a fronto-central voltage distribution, similar to what we report here (Etchell et al, 2012; Greenhouse and Wessel, 2013; Johnstone et al, 2007; Kok et al, 2004; Kramer et al, 2011; Lavallee et al, 2014; Nigbur et al, 2011; Schmiedt-Fehr and Basar-Eroglu, 2011; Wessel and Aron, 2013; Yamanaka and Yamamoto, 2010). However, due to the inverse problem, it is still unclear which exact anatomical brain regions generate this fronto-central activity.…”
Section: Discussionsupporting
confidence: 88%
“…Activity within this stopping network has been found across several brain imaging modalities. In the human scalp electroencephalogram (EEG), time-frequency analyses show a signature of successful action-stopping at fronto-central scalp sites, specifically within the theta- (5–8Hz) and delta-frequency bands (1–4Hz) (Lavallee et al, 2014; Nigbur et al, 2011; Schmiedt-Fehr and Basar-Eroglu, 2011; Wessel and Aron, 2013; Yamanaka and Yamamoto, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Processes related to the conflict monitoring modulate theta activity (Cohen & Donner, 2013;Lavallee et al, 2014;Tang et al, 2013;Wang et al, 2014). In the high baseline group, no such differences between compatible and incompatible Nogo trials were observed.…”
Section: Resting Theta Activity Groupingmentioning
confidence: 82%
“…The relationship between motion and EEG power might explain the lack of distinct correlation patterns found between specific frequency bands and BOLD responses (de Munck et al, 2009;Lavallee et al, 2014;Mantini et al, 2007), the lack of correlation of oscillatory EEG power in taskactive regions (Ritter et al, 2009;Scheeringa et al, 2009), and the high variability in correlation patterns across participants (de Munck et al, 2007;de Munck et al, 2009;Goncalves et al, 2006;Laufs et al, 2006a;Meyer et al, 2013). In particular, we suggest that EEG-fMRI studies investigating the relationship between oscillatory EEG power and BOLD responses in resting state are particularly susceptible to spurious correlations, since in resting state studies, continuous power time series are typically correlated with BOLD time series similar to the analysis presented here.…”
Section: Impact Of Motion On Simultaneous Eeg-fmri Studiesmentioning
confidence: 99%